SPLReePlan - Automated Support for Software Product Line Reengineering Planning - Marchezan, Luciano; Assunção, Wesley Klewerton Guez; Carbonell, João; Rodrigues, Elder; Bernardino, Maicon; Basso, Fábio (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2021)
The extractive adoption of Software Product Lines (SPL) relies on the reuse of the already developed systems, employing a reengineering process. However, due to the diversity of options found in the daily practice of SPL development, rigorous planning of scenarios is critical to perform SPL reengineering. This diversity is the result of different organizational aspects, such as team experience and product portfolio. Hence, a proper planning process must consider technical and organizational aspects, however, most existing studies in the field do not take into account organizational aspects of the companies. In this work, we present SPLReePlan, an automated framework to aid the SPL reengineering planning taking into account technical and organizational aspects. Our framework is supported by a web-based tool, ready to be used in the industry. To investigate how flexible is SPLReePlan to support the SPL reengineering planning in diverse situations, we extracted eight different scenarios from the SPL literature, which are used as input for the evaluation of SPLReePlan. The results indicate that SPLReePlan can be satisfactorily customized to a variety of scenarios with different artifacts, feature retrieval techniques, and reengineering activities. As a contribution, we discuss the lessons learned within the evaluation, and present challenges that were faced, being a source of information for tool builders or motivating new studies.